Update on Staphylococcus aureus bacteraemia. Issue 5 (4th October 2022) - Tabah, Alexis; Laupland, Kevin B.
Abstract : Purpose of review: To review recently published evidence relevant to Staphylococcus aureus bacteremia (SAB). Recent findings: Staphylococcus aureus is the most common pathogen causing co-infections and superinfections in patients with COVID-19. Methicillin-resistant Staphylococcus aureus (MRSA) bacteremia ratios have sharply risen during the pandemic. SAB mortality is 18% at 1 month and 27% at 3 months but has gradually decreased over the last 30 years. Recurrences and reinfections are common (9%). Standardised items to define complicated SAB, and a new cut-off defining persisting bacteremia after 2 days with positive blood cultures have been proposed. Multiple antibiotic combinations have been trialled including vancomycin or daptomycin with β-lactams, fosfomycin, or clindamycin, without significant results. In the recently published guidelines, vancomycin remains the first line of treatment for MRSA bacteremia. For the management of methicillin-susceptible Staphylococcus aureus, cefazolin less frequently causes acute kidney injury than flucloxacillin, and when susceptibility is demonstrated, de-escalation to penicillin G is suggested. Summary: Our review confirms that Staphylococcus aureus represents a special aetiology among all causes of bloodstream infections. Pending results of platform and larger trials, its distinct epidemiology and determinants mandate careful integration of clinical variables and best available evidence to optimize patient outcomes.